Modern Solutions for Treating Nose Injuries - Ergashevich, Qiyomov Ikhtiyor (Journal of Science in Medicine and Life, 2024)
Depending on the surgical method, the following types of septoplasty are distinguished: Ultrasonic. Recommended for C-shaped curvature. Radio wave. Surgitron corrects curvature without affecting cartilage and bone tissue. Classic. It is characterized by removing the curvature of the bone by removing the cartilage. At the end of the process, a plate is installed that sets the desired position. Often the tip of the nose hangs. The downside is a lot of blood loss.